2012
DOI: 10.1353/jhr.2012.0028
|View full text |Cite
|
Sign up to set email alerts
|

Does Stock Market Performance Influence Retirement Intentions?

Abstract: Media reports predicted that the stock market decline in October 2008 would cause changes in retirement intentions, due to declines in retirement assets. We use panel data from the Health and Retirement Study to investigate the relationship between stock market performance and retirement intentions during 1998-2008, a period that includes the recent crisis. While we find a weak negative correlation between stock returns and retirement intentions, further investigation suggests that this relationship is not dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…We find no effects of the economic indicators on plans to stop working or on expected age to stop working. These results differ from those of earlier HRS studies that reported that stock market and unemployment changes influenced the probability of working past age 62 and 65 (Goda et al, 2010(Goda et al, , 2011; however, we excluded partial retirees, whereas past research using the HRS did not. More research is needed to explore why the recession seems to have had little impact on plans to stop working or the age at which workers plan to stop.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…We find no effects of the economic indicators on plans to stop working or on expected age to stop working. These results differ from those of earlier HRS studies that reported that stock market and unemployment changes influenced the probability of working past age 62 and 65 (Goda et al, 2010(Goda et al, , 2011; however, we excluded partial retirees, whereas past research using the HRS did not. More research is needed to explore why the recession seems to have had little impact on plans to stop working or the age at which workers plan to stop.…”
Section: Resultscontrasting
confidence: 99%
“…Both the 2000 stock market decline and the recession that began in late 2007/early 2008 led to steep drops in some retirement portfolios and assets (Eschtruth & Gemus, 2002;McFall, 2011), particularly for younger workers with defined contribution rather than defined benefit pension plans (Gustman, Steinmeier, & Tabatabai, 2009a). Stock market declines have been shown to lead workers to postpone the actual and expected timing of their retirement, although effects have been relatively small (Bosworth & Burtless, 2010;Coile & Levine, 2006Goda et al, 2010Goda et al, , 2011Munnell, Muldoon, & Sass, 2009). Rising unemployment during recessions can undermine workers' opportunities to extend their working lives.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimates from Bosworth and Burtless (2010) suggest that a one standard deviation (more than 10 percentage points over three years) decrease in asset returns would increase labor force participation for those age 55 to 59 by only 0.2 to 0.4 percentage points. Other studies find no statistically significant relationship between stock market indices and retirement probabilities (Hurd and Reti 2003;Hurd, Reti, and Rohwedder 2009;Coile and Levine 2006;Goda, Shoven, and Slavov 2010). Even in the Great Recession, McFall (2011) and Gustman, Steinmeier, and Tabatabai (2010) project only a small increase in the retirement age.…”
Section: Probit Regression Resultsmentioning
confidence: 92%